Bio-energy with carbon capture and storage (BECCS): Opportunities for performance improvement. (1st February 2018) - Bui, Mai; Fajardy, Mathilde; Mac Dowell, Niall
Highlights: With heat recovery, carbon negative power plants can be 38%HHV efficient. BECCS plant efficiency and carbon negativity are strongly related. Sustainably sourced biomass is key to net atmospheric CO2 removal. Co-firing can reduce SOx formation. Abstract: This study evaluates the performance of a 500 MW pulverised fuel BECCS system. A performance matrix is developed to assess the opportunities for BECCS performance improvement in terms of: energy efficiency, carbon intensity, and pollutant emissions. The effect of fuel properties was analysed for variable (i) coal type (high/medium sulphur content), (ii) biomass type (wheat straw and wood chips), (iii) moisture content, and (iv) biomass co-firing proportion %. It was observed that the co-firing of biomass increased the quantity and quality of waste heat available for recovery from the exhaust gas. The opportunities to improve energy efficiency in the BECCS system include enhancing heat recovery and using high performance solvents for CO2 capture, such as biphasic materials. Implementing these approaches increased the power generation efficiency from 31%HHV (conventional MEA system) to 38%HHV (using an advanced biphasic solvent with heat recovery). Furthermore, power generation efficiency was found to influence the carbon intensity on an annual basis and annual capacity (load factor) of the BECCS system. Significant reductions to SOX emissions were achieved by increasing biomass co-firing % or using low sulphur coal.